2023
DOI: 10.1186/s40942-023-00513-5
|View full text |Cite
|
Sign up to set email alerts
|

Anterior migration of Ozurdex implant: a review on risk factors, complications, and management

Panagiotis Tsoutsanis,
Dimitrios Kapantais

Abstract: Purpose To describe the common risk factors, complications, and management options for anterior migration of Ozurdex implant. Methods A comprehensive review of the literature was performed. Results Amongst the most common risk factors predisposing to implant anterior migration we found a history of pseudophakia or aphakia or previous vitrectomy. The most common complication is that of corneal edema. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The CSs have a strong immunosuppressive action, so they can exacerbate all types of infections, and case reports of reactivation of ocular herpetic infection [70] or of acute retinal necrosis [75] after Ozurdex IV implant have been described. d Aphakia, absence or interruption of the posterior capsule, large iridectomy: All these conditions are associated with the risk of the implant migration into the anterior chamber, which has been described both for Ozurdex [172] and for Iluvien [173]. The migration of the implant into the anterior chamber can lead to localized or diffuse corneal edema due to endothelial cell loss, which may be related to the chemical toxicity of the implant components or to the mechanical trauma of the rigid device in contact with the cornea [172,173].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The CSs have a strong immunosuppressive action, so they can exacerbate all types of infections, and case reports of reactivation of ocular herpetic infection [70] or of acute retinal necrosis [75] after Ozurdex IV implant have been described. d Aphakia, absence or interruption of the posterior capsule, large iridectomy: All these conditions are associated with the risk of the implant migration into the anterior chamber, which has been described both for Ozurdex [172] and for Iluvien [173]. The migration of the implant into the anterior chamber can lead to localized or diffuse corneal edema due to endothelial cell loss, which may be related to the chemical toxicity of the implant components or to the mechanical trauma of the rigid device in contact with the cornea [172,173].…”
mentioning
confidence: 99%
“…d Aphakia, absence or interruption of the posterior capsule, large iridectomy: All these conditions are associated with the risk of the implant migration into the anterior chamber, which has been described both for Ozurdex [172] and for Iluvien [173]. The migration of the implant into the anterior chamber can lead to localized or diffuse corneal edema due to endothelial cell loss, which may be related to the chemical toxicity of the implant components or to the mechanical trauma of the rigid device in contact with the cornea [172,173]. e Presence of DME associated with advanced DR or with PDR: Previous studies have shown that both IV anti-VEGF (ranibizumab and aflibercept) [53,54] and IV CSs (TA, Ozurdex, and Iluvien) [46,174,175] used for the treatment of DME were able to simultaneously reduce the risk of DR progression and PDR development.…”
mentioning
confidence: 99%